2012
DOI: 10.1007/s10461-012-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

Versatility and HIV Vulnerability: Patterns of Insertive and Receptive Anal Sex in a National Sample of Older Australian Gay Men

Abstract: According to mathematical modeling, HIV is more likely to spread through a population of men who have sex with men when high numbers practice versatile anal sex roles, that is, engage in both insertive (IAI) and receptive anal intercourse (RAI). Yet, actual patterns of versatility remain largely unknown, particularly among older men who currently face growing rates of HIV. In this study, 1,135 Australian gay men aged 40 years and older completed a national online survey of their sexual health and behavior over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
1
11
0
4
Order By: Relevance
“…It is possible that the decline in penile wart may due to the herd protection in bisexual MSM during penile-vaginal sex. Furthermore, the majority of MSM are usually versatile (engaged in both insertive and receptive anal sex), only a small proportion (<25%) of MSM had insertive anal sex only 17. Given that anal wart is more common than penile wart in MSM, and it is extremely rare to have both penile and anal wart among individuals, it is suggested that the anal epithelium may be more susceptible to warts than the penile epithelium 18…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the decline in penile wart may due to the herd protection in bisexual MSM during penile-vaginal sex. Furthermore, the majority of MSM are usually versatile (engaged in both insertive and receptive anal sex), only a small proportion (<25%) of MSM had insertive anal sex only 17. Given that anal wart is more common than penile wart in MSM, and it is extremely rare to have both penile and anal wart among individuals, it is suggested that the anal epithelium may be more susceptible to warts than the penile epithelium 18…”
Section: Discussionmentioning
confidence: 99%
“…Yet research indicates that the majority of GBM self-identify as versatile (Hart et al, 2003), and practice sexual versatility. For example, in a national Australian on-line survey of GBM over forty years of age (n=1,135) 62% of participants engaged in insertive and receptive anal sex in the past year (Lyons et al, 2013), while another Australian study of over 800 GBM reported that 20% practiced versatility in their last anal sex episode (Lyons et al, 2011). An additional limitation is that event-level studies usually gather data only on participants’ sexual behavior and substance use, not their partners’ (for an exception see Colfax et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Gay men also account for the largest proportion of HIV infections in developed countries [15] and have disproportionately high rates of other STIs [16,17]. Given that large numbers continue to engage in unprotected sex with casual partners [18][19][20][21], the impact on current and future epidemics from partnership patterns such as sexual concurrency could be considerable [10,12,22,23]. Despite this, relatively little is known about the prevalence of sexual concurrency and its correlates among gay men.…”
Section: Introductionmentioning
confidence: 99%